Murder Legendre’s Dead: How White Zombie Challenges Critical Influence and Reinforces Racial Anxieties - Lambert, Heather (Hungarian Journal of English and American Studies, 2022)
How does a film achieve success with audiences, and what factors influence that success? Victor Halperin’s 1932 horror film White Zombie was derided by critics at the time of its release, while at the same time attaining financial victory at the box office. As such, White Zombie serves as a key source for exploring these critical questions. This analysis of the evolution of White Zombie’s reception from the 1930s to the present through the study of archival documents reveals the influential role advertising—specifically advertising that taps into cultural fascinations and anxieties—has over critical reviews. This is found to be especially true within the B-film horror genre, with its tendency to draw a cult following despite its lack of technical mastery, providing a larger commentary on what the public values in horror films. (HL)